PENGARUH PENGGUNAAN TEPUNG BELALANG (Locusta migratoria) DALAM PAKAN TERHADAP PERFORMA DAN LEMAK ABDOMINAL AYAM KAMPUNG JANTAN - , JAMALUDIN GHIFARI, Prof. Dr. Ir. Zuprizal, DEA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The experiment was conducted to know the effect of using grasshopper meal (Locusta migratoria) in the ration on the performance and abdominal fat deposition on male Native Chicken. Fourty five male Native Chicks two weeks of age were divided randomly into five treatments, in three replications with three chickens each. The diets treatments were R0, R1, R2, R3 and R4, consisting of grasshopper meal 0